Korelasi Hak Asasi Manusia dan Hukum Islam - Daniel Alfaruqi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2017)
Abstract.The controversy between Islamic law and universal human rights continues to roll. Apart from universal claims to human rights principles, when he saw that the concept came from the West, some Muslims were suspicious and considered it an attempt to secularize Islamic law. As a result, conservative Muslims continue to reject the application of Western standards, even in the name of universal human rights, to legal problems in Muslim societies. Based on this research, it can be concluded that the Islamic response to human rights is a reflection of global, lasting and fundamental demands. By not intending to have anology, in fact Islam has first taught humanity about concepts that are egalitarian, universal and democratic. This concept that is so beautiful and comprehensive is allegedly adopted by the West through the emergence of universal ideas standardized in the convention of the Universal Declaration of Human Rights. Islamic teachings cover all aspects of human life, and of course they have included rules and high respect for human rights. But it is not in a structured document, but is spread in the holy verses of the Qur'an and the Sunnah of the Prophet Muhammad. The birth of the UDHR and the Cairo Declaration on Human Rights in Islam (CDHRI) endorsed by the OIC was an attempt to clarify the actions of Muslim countries on arrogant, authoritarian and arbitrary Western claims.Keywords: Islamic law, human rights Abstrak.Kontroversi antara hukum Islam dan hak-hak asasi manusia universal terus bergulir. Meskipun telah melekat klaim universal pada prinsip-prinsip HAM, ketika melihat bahwa konsep tersebut berasal dari Barat, sebagian umat Islam curiga dan menganggapnya sebagai usaha untuk mensekulerkan hukum Islam. Karena itu, kalangan Muslim konservatif tetap menolak penerapan standar-standar Barat, meskipun atas nama HAM universal, terhadap persoalan-persoalan hukum pada masyarakat Muslim. Berdasarkan penelitian ini diperoleh kesimpulan bahwa respon Islam terhadap hak asasi manusia adalah cerminan dari tuntutan global, abadi, dan fundamental. Dengan tidak bermaksud untuk berapologi, sesunguhnya Islam telah terlebih dahulu mengajarkan umat manusia tentang konsep yang egaliter, universal, dan demokratis. Konsep yang sedemikian indah dan komprehensif ini disinyalir diadopsi oleh Barat melalui pemunculan ide-ide universal yang dibakukan dalam konvensi Universal Declaration of Human Rights. Ajaran Islam meliputi seluruh aspek dari sisi kehidupan manusia,dan tentu saja telah tercakup di dalamnya aturan dan penghargaan yang tinggi terhadap hak asasi manusia (HAM). Namun memang tidak dalam satu dokumen yang terstruktur, tetapi tersebar dalam ayat-ayat suci al-Quran dan Sunnah Nabi Muhammad SAW. Kelahiran UDHR dan Cairo Declaration on Human Rights in Islam (CDHRI) yang diratifikasi oleh OKI merupakan upaya penjernihan yang dilakukan oleh negara-negara Muslim atas klaim Barat yang arogan, otoriter dan semena-mena.Kata kunci: Hukum Islam, Hak Asasi Manusia